Radiosensitivity test on two varieties of Terengganu and Arab used in mutation breeding of roselle (Hibiscus sabdariffa L.) - S.S, Harding; Osman, Mohamad (Academic Journals, 2009)
A study was carried out in a greenhouse to determine the effective doses for mutation breeding of roselle during the year 2006/2007. Seedling height was the parameter recorded at 2, 3, 4 and 5 weeks after sowing of M1 seeds of 2 varieties Terengganu and Arab. The results indicated that increasing doses of gamma irradiation from 0 to 1200 Gy in steps of 100 Grey (Gy) caused increasing physiological effect on seedling height. There was a progressive increase in seedling height from 2 until 5 weeks after sowing. However, at week 2 and 3 after sowing there was no significant difference between seedling heights. The LD50 values determined from regression analyses for Terengganu based on seedling height were 754, 821.4, 761.7 and 766.7% at 2, 3, 4 and 5 weeks after sowing, respectively and the LD50 values for Arab were 773.8.%, 804.1.%, 704.2 and 708.3% at 2, 3, 4 and 5 weeks, respectively. 2 weeks after sowing appears to be the most appropriate time for data collection. The LD50 values at 2 weeks were not significantly different from 3, 4 and 5 weeks after sowing. The LD50 values for Terengganu and Arab determined at 2 weeks were 754 and 773.8%, respectively.